Produksi Sabun Alami Dari Lidah Buaya dan Temu Giring Dengan Metode Cold Process: - - Nurul Muti'ah; Endang Setia Muliawati; Dyah Ayu Suryaningrum (Journal of Applied Agriculture, Health, and Technology, 2022)
Soap has been used to care for and protect skin health. It is now becoming a daily need for society, thus the demand increase year by year. People nowadays have been more aware of the ingredients used in soap as the healthy and eco-friendly lifestyle become popular. Soap is needed as a natural treatment innovation for the cleanliness and health of the body's skin. The study was aimed to obtain the natural soap formulation from three comparisons of formulas with natural ingredients of aloe vera and temu giring (Curcuma heyneana). Aloe vera consists of saponins that have ability to clean dirt and act as an antiseptic, meanwhile Curcuma heyneana can be used to moisturize the skin and remove dead skin cells. The method use in this research is the cold process, which applies low temperatures during the curing process. Soap development was started by mixing coconut oil, olive oil, NaOH, distilled water, aloe vera, and Curcuma heyneana is, then continued by the curing process. Soap formulations were divided into three plans with differences in the ingredients and volume. The recommended formulation has found in formulation III, with details of 14 ml coconut oil, 14 ml olive oil, 9.25 ml aquades, 2.75 ml NaOH, 2.75 ml aloe vera, 4.6 ml Curcuma heyneana, and orange essentials oil 2.75 ml. The soap product with the "Javalove" brand was formulated as an innovative use of Javanese natural ingredients in solid soap additives to help cleanse and smooth the body's skin.